Simulation of mechanical properties of Zr/ZrN and TiN/ZrN multilayers using the finite elements method (2010)
This paper presents the study of mechanical properties of multilayers of Zr / ZrN and TiN / ZrN by varying the number of bilayers in 1, 2, 5 and 10, that is, periods of 2, 1, 0.4 and 0.2 μm, with a constant thickness of 2 μm in a ratio of 1: 1 and 1: 3. For this simulation, the ANSYS software was used, which is based on the finite element method. Effort curves were obtained - Deformation, hardness and Young's modulus depending on the number of bilayers. According to the analysis performed, the TiN / ZrN bilayers with a 1: 3 ratio have greater hardness (31 ± 1 GPa) in relation to the other systems and a Young's modulus of approximately 460 GPa. The results of the simulations of the mechanical properties of Ti and Zr-based materials, using methods such as finite elements, are promising in the field of new materials to predict their performance in technological and industrial applications such as hard coatings on different tools and pieces of machinery and thus reduce production costs. In addition, the simulations presented in this work can be extended to systems composed of other useful materials.